N-Butylpyridine-4-thiocarboxamide - C. Revathi; M. Hemalatha; A. Dayalan; M. N. Ponnuswamy; T. Kavitha (Acta Crystallographica Section E, 2008)
In the title molecule, C10H14N2S, the n-butyl chain assumes a trans zigzag conformation. The dihedral angle between the pyridine ring and the thioamide plane is 23.38 (8)°. The molecules in the crystal structure are linked by an intermolecular N—H...N hydrogen bond.